2013
DOI: 10.1080/09585192.2013.860389
|View full text |Cite
|
Sign up to set email alerts
|

Affective commitment and turnover intentions among healthcare professionals: the role of emotional exhaustion and disengagement

Abstract: This paper utilises the conservation of resources theory to examine the mediating role played by disengagement in the relationships between emotional exhaustion, affective commitment and turnover intentions among healthcare professionals. Structural equation modelling was conducted on data obtained from 302 healthcare professionals in a major Australian cancer hospital. Our findings demonstrate that disengagement fully mediates the relationships between emotional exhaustion and both affective commitment and tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
66
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(81 citation statements)
references
References 77 publications
(103 reference statements)
6
66
0
Order By: Relevance
“…Emotional exhaustion, the core dimension of burnout [4], is not only detrimental to employees' physical and mental health, but is also harmful to enterprises' sustainable development. According to previous studies, employees who become emotionally exhausted display sabotage behaviors, poor performance, high turnover intentions, and so on [5][6][7]. Unfortunately, emotional exhaustion is a widespread phenomenon, especially among frontline service employees.…”
Section: Introductionmentioning
confidence: 99%
“…Emotional exhaustion, the core dimension of burnout [4], is not only detrimental to employees' physical and mental health, but is also harmful to enterprises' sustainable development. According to previous studies, employees who become emotionally exhausted display sabotage behaviors, poor performance, high turnover intentions, and so on [5][6][7]. Unfortunately, emotional exhaustion is a widespread phenomenon, especially among frontline service employees.…”
Section: Introductionmentioning
confidence: 99%
“…It is also observed that staff turnover is the proportion of staff leaving in a given time period but prior to the anticipated end of their contract (Hom, Griffeth, & Gaertner, 1994). Facing the high labour turnover is a major issue for the apparel industry because employee turnover is a serious problem for the organizations in terms of the need to recruit and train employees (Thanacoody, Newman, & Funchs, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Withinperson analyses have yielded similar findings, linking negative affect to work withdrawal among a sample of bus drivers (Scott & Barnes, 2011). A recent study provided evidence that disengagement mediated the relationship between emotional exhaustion and withdrawal cognitions such as affective commitment and turnover intentions among a sample of health care workers (Thanacoody, Newman, & Fuchs, 2014). These studies collectively suggest that various forms of withdrawal are common responses to resource depletion and self-regulation impairment.…”
Section: Withdrawalmentioning
confidence: 73%